2019
DOI: 10.3390/nano9121665
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antibacterial Reagents (Centella, Propolis, and Hinokitiol) Loaded into Poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate] Composite Nanofibers for Biomedical Applications

Abstract: Centella asiatica, propolis, and hinokitiol, as natural antibacterial reagents, were integrated into the poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate] (PHBH) polymer to produce antibacterial wound dressings, using electrospinning process. The results showed that the fiber diameters and surface morphology of PHBH composite nanofibers were influenced by the addition of ethanol–centella (EC), methanol–centella (MC), ethanol–propolis (EP), and ethanol–hinokitiol (EH) at various ratios compared to pristine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…mollis nanofibers' spectrum. However, the spectrum of raw CA confirms its characteristics peaks at 3322.12 cm −1 (O-H stretching vibration of carboxylic acid group), 1656.07 cm −1 (C-O stretching vibration), 1451.17 cm −1 (C-H in-plane bending vibration), 1375.48 cm −1 (C-N stretching vibration, aromatic amide), and 1024.98 cm −1 (C-O stretching) [49].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 63%
See 1 more Smart Citation
“…mollis nanofibers' spectrum. However, the spectrum of raw CA confirms its characteristics peaks at 3322.12 cm −1 (O-H stretching vibration of carboxylic acid group), 1656.07 cm −1 (C-O stretching vibration), 1451.17 cm −1 (C-H in-plane bending vibration), 1375.48 cm −1 (C-N stretching vibration, aromatic amide), and 1024.98 cm −1 (C-O stretching) [49].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 63%
“…A similar effect was previously reported by Amina et al [ 48 ], who showed that the characteristic peaks of PU nanofibers overlapped with the bands of aqueous extract of Grewia mollis ( G. mollis ), leading to a higher intensity in the PU/ G. mollis nanofibers’ spectrum. However, the spectrum of raw CA confirms its characteristics peaks at 3322.12 cm −1 (O-H stretching vibration of carboxylic acid group), 1656.07 cm −1 (C-O stretching vibration), 1451.17 cm −1 (C-H in-plane bending vibration), 1375.48 cm −1 (C-N stretching vibration, aromatic amide), and 1024.98 cm −1 (C-O stretching) [ 49 ].…”
Section: Resultsmentioning
confidence: 83%
“…The primary structure of PHAs critically influences the physical properties of the material. For example, a random copolymerization of 3-hydroxybutyrate (3HB) and 3-hydroxyhexanoate (3HHx) units with controlled composition is effective for regulating the crystallinity of the polymer so that the P(3HB- co -3HHx) copolymer possesses a flexible mechanical property that can be adjusted for various uses, such as a mono-material ( Wong et al, 2012 ), composite ( Rebia et al, 2019 ), or blend ( Ivorra-Martinez et al, 2020 ). Therefore, engineering the PHA structure is important for expanding its range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Placing intracanal medicaments is one of the most conservative methods for reducing the microbial load and incidence of interappointment pain. In vitro studies regarding the anti-microbial [16,27,28], anti-inflammatory [29,30], and biocompatibility [31] properties along with other benefits of propolis due to its antioxidant effects have shown immense potential [32]. However, the effect of propolis on post-instrumentation pain was unknown.…”
Section: Discussionmentioning
confidence: 99%